Legionella pneumophila regulates the activity of UBE2N by deamidase‐mediated deubiquitination. (11th December 2019) - Gan, Ninghai; Guan, Hongxin; Huang, Yini; Yu, Ting; Fu, Jiaqi; Nakayasu, Ernesto S; Puvar, Kedar; Das, Chittaranjan; Wang, Dongmei; Ouyang, Songying; Luo, Zhao‐Qing
Abstract: The Legionella pneumophila effector MavC induces ubiquitination of the E2 ubiquitin‐conjugating enzyme UBE2N by transglutamination, thereby abolishing its function in the synthesis of K63 ‐type polyubiquitin chains. The inhibition of UBE2N activity creates a conundrum because this E2 enzyme is important in multiple signaling pathways, including some that are important for intracellular L. pneumophila replication. Here, we show that prolonged inhibition of UBE2N activity by MavC restricts intracellular bacterial replication and that the activity of UBE2N is restored by MvcA, an ortholog of MavC (50% identity) with ubiquitin deamidase activity. MvcA functions to deubiquitinate UBE2N‐Ub using the same catalytic triad required for its deamidase activity. Structural analysis of the MvcA‐UBE2N‐Ub complex reveals a crucial role of the insertion domain in MvcA in substrate recognition. Our study establishes a deubiquitination mechanism catalyzed by a deamidase, which, together with MavC, imposes temporal regulation of the activity of UBE2N during L. pneumophila infection. Synopsis: Transglutaminase MavC of the bacterial pathogen Legionella pneumophila catalyzes atypical ubiquitination of the host cell E2 ubiquitin conjugation enzyme UBE2N. Here, the L. pneumophila ubiquitin deamidase MvcA is found to reverse MavC‐induced UBE2N ubiquitination and to restore its activity to promote host cell survival at later stages of L. pneumophila infection. Expression of MvcA reduces MavC‐induced UBE2N ubiquitination. MvcA promotes synthesis of K63‐type polyubiquitin chains by UBE2N during L. pneumophila infection. MvcA is a UBE2N‐specific deubiquitinase that cleaves the isopeptide bond between Gln40 of ubiquitin and Lys92 of UBE2N. Structure of the MvcA‐UBE2N‐Ub complex reveals involvement of the MvcA "insertion domain" in substrate recognition. MvcA counteracts MavC activity at the late stage of infection to promote intracellular replication of L. pneumophila . Abstract : Dynamic regulation of activity and atypical ubiquitination of the host E2 enzyme UBE2N via bacterial effectors MavC and MvcA over the course of infection is important for pathogen replication.